Eagle’s syndrome – A report of two cases - Kiralj, Aleksandar; Ilić, Miroslav; Pejaković, Bojan; Markov, Borislav; Mijatov, Saša; Mijatov, Ivana (Vojnosanitetski pregled, 2015)
Introduction. Eagle’s syndrome is defined as elongation of the styloid process or the stylohyoid ligament mineralization complex which consist of styloid process, stylohyoid ligament and lesser horn of hyoid bone. It is a rare entity, is not commonly suspected in clinical practice. It is characterized by recurrent facial and throat pain, dysphagia, odynophagia, parapharingeal foreign body sensation, otalgia and neck pain. Eagle’ş syndrome can be treated conservatively (lacing local anesthetic into the styloid process and stylomandibular ligament attachment) or surgically. Its pathogenesis and threatment modalities are still being debated while different theories have been presented. Case report. The two traditional surgical approaches to styloidectomy (removal of the elongated portion of the styloid process) were presented the intraoral approach and the extraoral approach. We presented two cases (49 years and 34 years old males), with bilateral and unilateral elongated styloid process. The surgical treatment included unilateral right side stiloidectomy by intraoral approach in the first case and right styloidectomy by extraoral approach in the second case. In both eases postoperative course passed regularly with no complaints at regular postoperative control. Conclusion. Surgical techniques for treatment of Eagle’s syndrome have many advantages and disadvantages. We believe that the length of the styloid process or the calcified ligament is a decisive parameter for the selection of techniques and approach.
Keywords: temporomandibular joint disorders; diagnostic techniques and procedures; oral surgical procedures